Achieving Correct Balance in Total Knee Arthroplasty with Fixed Varus Deformity - Sarrel, Kara; Weinberg, Maxwell; Scuderi, Giles (The Journal of Knee Surgery, 2023)
Varus knee deformity is one of the most common deformities presenting for total knee arthroplasty (TKA). When present, a varus knee deformity contributes to overload of the medial joint compartment during gait, leading to increased medial compartment forces as well as lateral soft tissue lengthening. Additionally, a fixed varus deformity is associated with medial soft tissue contractures of the deep and superficial medial collateral ligament (MCL) and posteromedial capsule. With a fixed varus deformity, soft tissue releases may be necessary to create equivalent and rectangular flexion and extension gaps. There may also be anteromedial tibial bone defects, medial femoral condyle defects, and occasionally flexion contractures, especially in more severe cases. In cases of severe varus deformity with medial tibial bone loss, bone defects must be addressed to ensure adequate implant support. In many cases, a primary knee implant can be utilized in cases of varus knee deformity, but occasionally prostheses with higher levels of constraint may be required to balance and stabilize the knee. TKA has had a successful track record, with high levels of long-term implant survivorship even in cases of severe varus. Iatrogenic MCL instability and tibial aseptic loosening are complications associated with TKA in cases of severe varus, and multiple methods to avoid complications are presented here.
Keywords: orthopaedic surgery; adult reconstruction; arthroplasty; joint replacement; total knee arthroplasty